The Role of Management Accounting : It's Implementation In The Public Sector - Sabeni, Arifin (JURNAL BISNIS STRATEGI, 1999)
Many  definitions of management accounting  exist,  and  although  these  lack of complete  agreement,   it is possible   to say  that  management  accounting  plays important  roles  in an organization.  Particularly,   it plays in the managerial tasks of planning,   controlling,   and  decisionmaking. All organizations  need to  make  decisions and need to plan and control their activities, and all organizations,  whether they be in the private or the public sector,  ought to be able to benefit from  the use  of such management accounting techniques.   However,   the management accounting literature and the development of the techniques of management accounting  are almost exclusively concerned with a private sector environment. Little  discussions  are placed on  the public sector  environment.  For this reason,  the purpose of this paper  is to discuss  the role and  operation  of management  accounting in  the  public sector.  In so  doing,   this paper;   firstly,   discusses  the role of management accounting  in  an  organization,   then,   the role and operation of management accounting in the public sector. After that,  in order to give a comparison between theory  and practice,  this paper describes the actual practice of the role and operation of management  accounting  in the New  South   Wales   Department  of  Education as an illustration.   Furthermore,  such evaluation of management  accounting practices  in  the public  sector  are dis cussed;   andfinally;  summary and conclusion.